Modeling the Real-Time use of Reserves in the Joint Energy and Reserve Hourly Scheduling of a Pumped Storage Plant. (January 2016) - Chazarra, Manuel; Pérez-Díaz, Juan I.; García-González, Javier; Helseth, Arild
Abstract: This paper studies the impact that different approaches of modeling the real-time use of the secondary regulation reserves have in the joint energy and reserve hourly scheduling of a price-taker pumped-storage hydropower plant. The unexpected imbalance costs due to the error between the forecasted real-time use of the reserves and the actual value are also studied and evaluated for the different approaches. The proposed methodology is applied to a daily-cycle and closed-loop pumped-storage hydropower plant. Preliminary results show that the deviations in the water volume at the end of the day are important when the percentage of the real-time use of reserves is unknown in advance, and also that the total income in all approaches after correcting these deviations is significantly lower than the maximum theoretical income.